Conversion of fly ash - an environmentally detrimental waste to zeolite beta (BEA) for commercial catalytic applications - Kasture, M. W.; Bokade, Vijay V.; Joshi, P. N. (Journal of the American Ceramic Society, 2005)
Zeolite beta (BEA) was synthesized hydrothermally using fly ash as a combined source of alumina and silica. The overall crystallization period required to obtain pure crystalline BEA zeolite was found to be slightly longer when fly ash was used. The physicochemical properties of BEA phases obtained using fly ash (FLBEA) and conventional source materials (CONBEA) were compared. The H/FLBEA catalyst has exhibited excellent catalytic performance in commercially important benzene isopropylation process. These results have demonstrated that converting fly ash into BEA zeolite not only alleviates the disposal problem but also turns an otherwise waste material into a marketable commodity.